1997
DOI: 10.1002/hep.510260430
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and iatrogenic spreading of liver-derived cells into peripheral blood of patients with primary liver cancer

Abstract: The prognosis for patients with primary liver cancer (PLC)Despite advances in the appraisal of the impact and role often depends on tumor recurrence and the development of of etiologic factors, improvement in diagnostic tools and surextrahepatic metastases, particularly after liver transplanta-gical and nonsurgical treatments, primary liver cancer (PLC), tion. We have developed a sensitive test to detect both sponta-the eighth commonest tumor worldwide, still represents a neous circulation of tumor cells and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 42 publications
(6 reference statements)
1
33
2
Order By: Relevance
“…However, it has been suggested that these invasive treatments may indeed induce tumor cell dissemination. 40,41 Probably, in immunocompetent individuals, the iatrogenic dissemination of cells is not relevant, but in subjects receiving immunosuppression with several agents this cell spread may increase the risk of presenting clinically apparent metastatic sites both inside and outside the liver. We do not ascribe the recurrences of other series to the application of coadjuvant treatment, but we have to stress that we did not perform any kind of adjuvant treatment and this has not prompted a significant recurrence rate or relevant tumor growth while waiting for OLT.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that these invasive treatments may indeed induce tumor cell dissemination. 40,41 Probably, in immunocompetent individuals, the iatrogenic dissemination of cells is not relevant, but in subjects receiving immunosuppression with several agents this cell spread may increase the risk of presenting clinically apparent metastatic sites both inside and outside the liver. We do not ascribe the recurrences of other series to the application of coadjuvant treatment, but we have to stress that we did not perform any kind of adjuvant treatment and this has not prompted a significant recurrence rate or relevant tumor growth while waiting for OLT.…”
Section: Discussionmentioning
confidence: 99%
“…Both kinds of cells may contribute to the positivity of hAFP mRNA. According to Louha M, not only liver surgery but also nonsurgical invasive managements such as needle liver biopsy or intervention therapies such as TACE, chemotherapy and ethanol ablation therapy, the increased shedding of either HCC cells or normal hepatocytes into circulation might contribute to the increase of detection rate of hAFP mRNA [38] . This was also the reason why we excluded those who had received these intervention therapies from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Witzigmarn obtained blood samples before and during the operation (after mobilization of the liver), and on the second postoperative day [39] . Louha obtained peripheral blood samples before treatment, 1 hour and 24 hours after percutaneous ethanol injection or TACE treatment [38] . Witzigmann obtained blood samples on the second day after TACE [39] .…”
Section: Discussionmentioning
confidence: 99%
“…However, a concern with the use of hepatic tumor cell lines, e.g. HepG2, is the possible risk in the transmission of potentially tumorigenic cells to patients (Louha et al 1997). Instead, primary human and xenogeneic hepatocytes are used in bioartificial systems which have been or are currently in various stages of clinical evaluation.…”
Section: Cell Sourcementioning
confidence: 99%